MEMPREDIKSI FAKTOR-FAKTOR YANG MEMPENGARUHI LOYALITAS KONSUMEN TERHADAP PEMBELIAN ONLINE: SUATU STUDI EMPIRIS - Jessica Suryadijaya; Natasya Metta Gunawan; Sabrina Oktaria Sihombing (Ultima Management : Jurnal Ilmu Manajemen, 2020)
Abstract– This study aims to test consumer loyalty to GrabFood in terms of security, privacy, service fulfillment, non decptionand satisfaction from GrabFood consumers themselves. The sampling design used is purposive sampling which is a nonprobability sampling. All research indicators come from previous studies. Before testing hypotheses using structural equation modeling, the reliability and validity tests were carried out. The results of this study indicate that there is a significant relationship between security and non-deception on consumer satisfaction, and not deception and fulfillment of services to loyalty, both directly and indirectly. Based on the results of this study also, it was said that between customer satisfaction and customer loyalty, there was a significant relationship. This study suggests factors that must be considered by an online business in gaining customer loyalty. Keywords: Consumer Satisfaction, Consumer Loyalty, Security, Fulfillment, Non Deception, Privacy